Vrácení daně z přidané hodnoty - Žáková, Marie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Bakalářská práce je zaměřena na daň z přidané hodnoty a její vracení. Jsou zde vysvětleny základy pojmy této oblasti v České republice, v Evropské unii a vybraných státech. Také je zde popsán celý proces vracení daně z přidané hodnoty. Dále se zabývá situacemi, které nastávají při uplatňování DPH v praxi.

This bachelor thesis focuses on the value added tax and erimbursement. The thesis includes the explanation of the basic terminology of the value added tax in Czech Republic, European union and selected countries. The thesis also describes the entire proces of value added tax refund. Thesis also deals with situations, that actually occur in application of VAT in practice.
Value Added Tax Refund
Keywords: daň z přidané hodnoty; vrácení DPH; daň z přidané hodnoty v EU; value added tax; value added tax refund; value added tax in EU